2014
DOI: 10.1002/for.2286
|View full text |Cite
|
Sign up to set email alerts
|

Forecasting Mixed‐Frequency Time Series with ECM‐MIDAS Models

Abstract: This paper proposes a mixed‐frequency error correction model for possibly cointegrated non‐stationary time series sampled at different frequencies. We highlight the impact, in terms of model specification, of the choice of the particular high‐frequency explanatory variable to be included in the cointegrating relationship, which we call a dynamic mixed‐frequency cointegrating relationship. The forecasting performance of aggregated models and several mixed‐frequency regressions are compared in a set of Monte Car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 37 publications
0
31
0
Order By: Relevance
“…As far as the long-run term in the ECM-MIDAS model is concerned, Götz et al (2014) discuss the choice of which high-frequency observation to include in z v t−1 . It is shown that it does not make any significant difference which observation enters the long-run term, in terms of forecasting performances, as long as the structures of the short-run dynamics terms are adapted accordingly.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As far as the long-run term in the ECM-MIDAS model is concerned, Götz et al (2014) discuss the choice of which high-frequency observation to include in z v t−1 . It is shown that it does not make any significant difference which observation enters the long-run term, in terms of forecasting performances, as long as the structures of the short-run dynamics terms are adapted accordingly.…”
Section: Resultsmentioning
confidence: 99%
“…Although we aim to forecast GNP growth rates, it is quite possible that GNP is cointegrated with one or more of the regressors. As was shown by Götz et al (2014), disregarding (including) a long-run relationship in the presence (absence) of cointegration worsens the forecasting performance considerably. Hence, all of the models, except for (4), i.e., the autoregressive one, are in an error-correction format, in which a long-run term (z v t−1 below) is either included (labeled 'a') or excluded ('b').…”
Section: Appendix Modelsmentioning
confidence: 89%
“…It is expected to have better estimating and forecasting ability than many other conventional models (Ghysels et al, 2004). Götz, Hecq, and Urbain (2014) report that the unrestricted MIDAS model suffers from parameter proliferation for samples of relatively small size, whereas MIDAS forecasts are robust to over-parametrization. Foroni, Marcellino, and Schumacher (2015) compare unrestricted-MIDAS (U-MIDAS) with MIDAS with distributed lag functions, and find that U-MIDAS performs better than MIDAS for small differences in sampling frequencies, but not with large differing sampling frequencies.…”
Section: Introductionmentioning
confidence: 99%
“…These notational conventions have become standard in the mixed-frequency literature and are similar to the ones in Götz, Hecq, and Urbain (2014), Clements and Galvão (2008, 2009) or Miller (2012.…”
Section: Notationmentioning
confidence: 99%